PP2C-like Promoter and Its Deletion Variants Are Induced by ABA but Not by MeJA and SA in Arabidopsis thaliana - Bhalothia, Purva; Sangwan, Chetna; Alok, Anshu; Mehrotra, Sandhya; Mehrotra, Rajesh (Frontiers in Plant Science, 2016)
Gene expression is mediated through interaction between cis regulatory elements and its cognate transcription factors. Cis regulatory elements are defined as non-coding DNA sequences that provide the binding sites for transcription factors and are clustered in the upstream region of genes. ACGT cis regulatory element is one of the important cis regulatory elements found to be involved in diverse biological processes like auxin response, salicylic acid response, UV light response, ABA response and jasmonic acid response .We identified through in silico analysis that the upstream region of protein phosphatase 2C (PP2C) gene has a distinct genetic architecture of ACGT elements. In the present study, the activation of the full length promoter and its deletion constructs like 900 base pair, 500 base pair, 400 base pair and NRM were examined by stable transformation in Arabidopsis thaliana using β glucuronidase as the reporter gene. Evaluation of deletion constructs of PP2C- like promoter was carried out in the presence of phytohormones like abscisic acid (ABA), salicylic acid (SA) and jasmonic acid (JA). Our result indicated that the full length and 900 base pair promoter-reporter constructs of PP2C-like promoter was induced in response to ABA but not to methyl jasmonate and salicylic acid.